2016
DOI: 10.1016/j.watres.2016.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of factors governing data quality of integrative samplers employed in environmental water monitoring

Abstract: Integrative sampling enables the collection of analyte mass from environmental liquids over extended timeframes from hours to months. While the incentives to complement or replace conventional, time-discrete sampling have been widely discussed, the data quality implications of employing alternative, integrative methods have not yet been systematically studied. A critical analysis of contemporary literature reports showed the data quality of integrative samplers, whether active-advection or passive-diffusion, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 47 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…Key, however, is an improved understanding of the comparability of different sampling strategies (spot, event triggered or passive) particularly for pollutants (e.g. acidic herbicides, metaldehyde) that are present episodically in river catchments (Roll and Halden 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Key, however, is an improved understanding of the comparability of different sampling strategies (spot, event triggered or passive) particularly for pollutants (e.g. acidic herbicides, metaldehyde) that are present episodically in river catchments (Roll and Halden 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…acidic herbicides, metaldehyde) that are present episodically in river catchments. 44 An additional use of passive samplers is to generate TWA concentrations that can be used in combination with in situ flow data to estimate monthly or annual fluxes of specific pollutants. 33 This information can be used to better inform environmental risk assessments at the catchment scale.…”
Section: Potential Use Of Passive Samplers In Routine Regulatory Monimentioning
confidence: 99%
“…For passive samplers, R S is governed by a host of factors, including advective transport to and around the device and the diffusive transport of the contaminant to and into the sorbent material, the latter being a function of properties including the chemical species, ambient temperature, and length of the diffusive path. The RSD associated with R S has been variously reported for several passive and active samplers for a diversity of target species and ambient conditions, as reviewed recently (Roll and Halden, 2016). One study reported a range of RSD values for the Membrane-Enclosed Sorptive Coating (MESCO) of 4 to 49% (Vrana et al, 2001), whereas another employing the Polar Organic Chemical Integrative Sampler (POCIS) showed values varying from 9 to 95% (Jacquet et al, 2014), a third using the Semipermeable Polymeric Membrane Device (SPME) showed values of 1 to 33% (Huckins et al, 1999), and a final study employing Diffusive Gradient Thin Films showed values varying from 2–49% (Villanueva et al, 2013).…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…This suggests that variance associated with R S can be expected to be less than those associated with the extraction and quantification methods. Comparing the RSD for the sampling rate of the IS2 with that of several passive samplers, the results for the IS2 are particularly favorable, because the positive-displacement pumping system that governs R S for the IS2 is independent of the influences of temperature, mixing, and analyte-specific chemistry that cause significant variance in R S values of passive samplers (Roll and Halden, 2016). …”
Section: 0 Results and Discussionmentioning
confidence: 99%